2015
DOI: 10.1586/17434440.2015.1030339
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer flow modulator stent technology: a treatment revolution for US patients?

Abstract: Thoracoabdominal aortic repair is a high-risk procedure in most experienced centers, not only because of anatomical complexity but also due to the fragility of the patients in whom these aneurysms occur. Such repairs are complex, time-consuming and impose a systemic injury upon the patients, regardless of whether the repair is performed by open surgery or via a fenestrated/branched technique. The substantive risks associated with such repairs include death, dialysis and paralysis. The multilayer flow modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…These results suggest that control of the hemodynamic parameters inside the sac cannot be achieved by intuitively setting the stent porosity, requiring a CFD tool to predict the hemodynamic environment. Currently, there are no clinical practice guidelines to specify which type of porous stent is most efficacious for reducing the AAA progression without increasing the risk of rupture 39 . Therefore the proposed methodology is needed to inform these decisions and to improve clinical outcomes from treatments using porous stents in complex AAAs.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that control of the hemodynamic parameters inside the sac cannot be achieved by intuitively setting the stent porosity, requiring a CFD tool to predict the hemodynamic environment. Currently, there are no clinical practice guidelines to specify which type of porous stent is most efficacious for reducing the AAA progression without increasing the risk of rupture 39 . Therefore the proposed methodology is needed to inform these decisions and to improve clinical outcomes from treatments using porous stents in complex AAAs.…”
Section: Resultsmentioning
confidence: 99%
“…It is designed to modulate blood-flow dynamics by relieving local peak wall shear stress (PWSS), achieving stabilization of aneurysm-sac or false lumen pressure and preserving branches patency. Aneurysm rupture is prevented while flow lamination allows for both aneurysm thrombosis and branch perfusion (14,15). The present study offers early-and mid-term results on 8 patients with complex iliac artery aneurysms treated with MFM.…”
Section: Introductionmentioning
confidence: 82%
“…The MFM is a new, unique device which is used for the treatment of complex aneurysms. Its usage has increased with time and is being more frequently reported in the literature (12)(13)(14)(15). In this study, we presented our early-and mid-term results on 8 patients treated with the MFM for IAA.…”
Section: Discussionmentioning
confidence: 99%
“…There was no paraplegia in this group of patients and no paraplegia or other spinal cord ischaemia after covering the intercostal artery, as permanent paraplegia after TEVAR is associated with the length of the thoracic aorta covered. Feezor et al [6] found that spinal cord ischaemia after TEVAR occurred when the distance between the stent graft and the proximal end of the abdominal cavity was 17.3 ± 21.8 mm, whereas no ischaemia was observed when the distance was 63.1 ± 62.9 mm (p = 0.0006). The coverage length threshold was 205 mm, and the sensitivity and specificity of predicting spinal cord ischaemia after TEVAR were 80 and 92.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%